THE THYMUS GLAND (THYMUS) ASPECTS IN CHILDREN (PART V). HORMONAL AND MORPHOLOGICAL INTERACTION OF THE THYMUS WITH THE NEUROENDOCRINE SYSTEM AND IN PARTICULAR WITH SOMATOTROPIC HORMONE AND INSULIN-LIKE GROWTH FACTOR - Наталья Николаевна Миняйлова; Юрий Иванович Ровда; Сергей Фадеевич Зинчук; Александра Евгеньевна Климанова; Вероника Павловна Строева; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2022)
The literature review includes data on the interaction of the thymus with the neuroendocrine system, hormonal and morphological relations between the thymus, somatotropic hormone and insulin-like growth factor (IGF), the effect of growth hormone (GH) to age-related thymus involution. The results of experimental studies and contradictory data to the effect of the somatotropic axis (receptor-GR/GR/IGF-1) on thymopoiesis, homeostasis of thymocytes and peripheral T cells are presented.